The Quality Improvement of Educator Recruitment and Selection System in Madrasah - Muhammad Munawir Pohan; M. Nurzen S (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2021)
This study describes the recruitment and selection of teachers at Private Madrasah Aliyah PTP-VI Berangir, North Labuhanbatu Regency, North Sumatra Province. This research was conducted using a qualitative method with a case study design. Data collection tools using interviews with the head of the foundation, the head of the madrasah, the deputy head of the madrasah in the field of curriculum, and certified teachers, observation, and documentation. The research procedures include theme selection, literature reading, formulation of research focus and problems, data collection, data improvement, data processing, data analysis, theoretical dialogue, triangulation of findings, and conclusions of research results. Data analysis techniques include data collection, reduction, presentation, and conclusion. The results of this study are: (1) announcements of teacher recruitment and selection are rarely read or seen by the general public or even though they have used social media Facebook; (2) the admissions experience a few obstacles, namely the many qualifications that are not following the requirements of the madrasah (3) the implementation of all tests involves the principal, madrasah principal, deputy head of the madrasah in the field of curriculum, and teachers who already have professional educator certificates; (4) the results of the selection are carried out by contacting directly the prospective teacher who has passed all the tests and who has the highest score.